Neural Mechanisms of Temporomandibular Joint and Masticatory Muscle Pain: A Possible Role for Peripheral Glutamate Receptor Mechanisms - David K Lam; Barry J Sessle; Brian E Cairns; James W Hu (Pain Research and Management)
The purpose of the present review is to correlate recent knowledge of the role of peripheral ionotropic glutamate receptors in the temporomandibular joint and muscle pain from animal and human experimental pain models with findings in patients. Chronic pain is common, and many people suffer from chronic pain conditions involving deep craniofacial tissues such as temporomandibular disorders or fibromyalgia. Animal and human studies have indicated that the activation of peripheral ionotropic glutamate receptors in deep craniofacial tissues may contribute to muscle and temporomandibular joint pain and that sex differences in the activation of glutamate receptors may be involved in the female predominance in temporomandibular disorders and fibromyalgia. A peripheral mechanism involving autocrine and/or paracrine regulation of nociceptive neuronal excitability via injury or inflammation-induced release of glutamate into peripheral tissues that may contribute to the development of craniofacial pain is proposed.